The interaction between ensemble and item representations in a temporally extended context - Şen, Umay. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
To date, research demonstrated that visual perceptual judgments are susceptible to information which is accumulated in the recent past. However, it is not well known how localization of a particular item of a set is affected by the information coming from previous trials within an experimental session. The present research investigated how accumulated information during an experimental session impacted spatial item representations. In the present study, participants reported the location of an item in one of two types of perceptual sets. While one group of trials was of randomly generated sets, the other trials consisted of spatial configurations that belonged to perceptual families. We specifically tested whether localization in the latter group of trials would be more accurate. Also, previous research had demonstrated that individuals high in working memory were more likely to utilize spatial configuration information in visual change detection tasks. Thus, in the current set of experiments, we explored whether there were individual differences in working memory capacity impacted how efficiently viewers utilized perceptual set information in spatial localization. Results demonstrated that people were more able to accurately localize items in perceptual set trials compared to random configuration trials; however, this effect was observed only for some perceptual sets and not all suggesting that perceptual characteristics of sets may be critical. We also found that visual working memory capacity did not selectively predict localization errors in perceptual set and random configuration conditions.
Keywords: Perceptual-motor learning.